2017
DOI: 10.1002/jum.14298
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Care Ultrasound in General Surgery Residency Training: A Proposal for Milestones in Graduate Medical Education Ultrasound

Abstract: The use of point-of-care ultrasound (US) in the clinical setting has undergone massive growth, although its incorporation into training and practice is variable. Surgeons are interested in using point-of-care US and can incorporate it effectively into clinical practice. However, the current state of point-of-care US training in general surgery is inadequate. The Accreditation Council for Graduate Medical Education introduced the Milestones Project to evaluate resident and fellow performance. Emergency medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Missed or incorrect diagnoses can have substantial adverse consequences for the patient. Numerous training guides are available, for example, in surgery residency, anesthesiology, pediatrics, emergency medicine, resource‐limited emergency physicians, critical care, and clinical practice . Hands‐on training is critical and represents an important medical application of diagnostic US (with attention to potential incidental findings of medical importance) .…”
Section: Discussion Of Us Safety In the Pocus Perspectivementioning
confidence: 99%
“…Missed or incorrect diagnoses can have substantial adverse consequences for the patient. Numerous training guides are available, for example, in surgery residency, anesthesiology, pediatrics, emergency medicine, resource‐limited emergency physicians, critical care, and clinical practice . Hands‐on training is critical and represents an important medical application of diagnostic US (with attention to potential incidental findings of medical importance) .…”
Section: Discussion Of Us Safety In the Pocus Perspectivementioning
confidence: 99%
“…Given the cost of HUDs, further studies are needed to assess the degree to which HUD access will improve trainee interpretive ability, especially as more training programs consider the creation of ultrasound curricula. 10,11,24,39,40 This study was unique because it followed interns over a year-long course that repeated the same material to assess rates of learning with repeated exposure. Learners improved their scores after the first, but not second, block.…”
Section: Discussionmentioning
confidence: 99%
“…A follow‐up study in 2010 showed that 64% of emergency medicine residency programs required more than 150 ultrasound examinations for competency, which was a considerable improvement from previous reports before the American College of Emergency Physicians statement . Recent literature regarding general surgery training calls for an urgent need for a standardized ultrasound curriculum such as inclusion in the Accreditation Council for Graduate Medical Education Milestones Project . Currently, most residents who are exposed to diagnostic or interventional ultrasound in otolaryngology do not log or track these procedures in a formal way.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent literature regarding general surgery training calls for an urgent need for a standardized ultrasound curriculum such as inclusion in the Accreditation Council for Graduate Medical Education Milestones Project. 7,8 Currently, most residents who are exposed to diagnostic or interventional ultrasound in otolaryngology do not log or track these procedures in a formal way. Encouragement of such a mechanism may be vital to legitimize and potentially credential our trainees as competent in performing ultrasound procedures.…”
Section: Discussionmentioning
confidence: 99%